Fatigue Communication Patterns in Interpersonal Communication in the Work Environment - Evi Sirait (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This study will look at the use of phatic communication in interpersonal relationships that occur in the workplace. The research method is descriptive qualitative. The result of the study is that the use of phatic communication is very often done in the workplace, as an opener for closer relationships. In fact, one's cultural context really plays a role in phatic communication activities. The conclusion of this study, phatic communication is very important in building and managing relationships in the workplace.